Impact of 12-s Rule on Performance and Muscle Damage of Baseball Pitchers. Issue 12 (December 2016) - YANG, SUN-CHIN; WANG, CHIA-CHI; LEE, SHIN-DA; LEE, YU CHUNG; CHAN, KUEI-HUI; CHEN, YI-LIANG; FOGT, DONOVAN L.; KUO, CHIA-HUA
ABSTRACT: Introduction: A recent US Major League Baseball (MLB) rule change requires baseball pitchers to deliver pitches within 12 s. Purposes: To examine the effect of three between-pitch rest intervals on throwing performance during a simulated seven-inning game and muscle damage during postgame recovery. Design: A randomized counterbalanced study. Methods: Seven intercollegiate pitchers threw 15 pitches per inning for seven innings with rest interval trials of 8, 12, and 20 s between pitches and 5 min between innings. Pitchers threw aimed fastballs at their best effort. Trials were separated by ≥2 wk. Results: Progressive decreases in pitching speed and accuracy below baseline (first inning of 20-s trial) occurred after fourth inning during the 8-s and 12-s trials, but not the 20-s trial. Plasma creatine kinase elevated 48 h later for the 8-s and 12-s trials (+105% and +75%, P < 0.01), but not the 20-s trial (+26%, no significance). A transient interleukin (IL)-6 surges immediately after the game for the 8- and 12-s trials (+265%, +128%, P < 0.01) above baseline. IL-6 reversed below the level of 20-s trial at 48 h after game, whereas IL-10 increased significantly above the level of 20-s trial. Conclusions: Under the same pitching load, decreasing rest interval from 20 to 12 s or less results in an early-onset performance loss during a game and increases in muscle damage and inflammation for more than 2 d after a game. Our data do not favor the current rule change in concern of keeping musculoskeletal health of pitchers.